Simulation protocol for core flooding: Relative permeability and capillary pressure analysis - Kumar, S. (Offshore Technology Conference, 2014)
The relative permeability and capillary pressures are used to characterize large-scale multiphase flow encountered in recovery of hydrocarbons. These parameters are acquired via special core flooding experiments. Reservoir engineers calculate these parameters from special core analysis (SCAL) module of reservoir simulation. However, core flooding is an expensive experiment and involves spending lot of time and efforts before Darcy law assumptions are achieved. Therefore, independent simulation of core flooding is necessary during which reservoir engineers can perform faster and simultaneous analysis of relative perms and capillary pressures of multiphase flow. This paper presents 1-D black oil simulation of core flooding using Sendra software to get relative perms and capillary pressures. The approach used in this study was four steps. In the first step, core flooding was simulated for particular scenario of injection using different correlations. In the second step, experimental data of core flooding for differential pressure and production versus time were referenced in the software. Then history matching was performed between estimated and experimental data of core flooding. Based on this, the best fit of correlations was obtained for estimating both relative perms and capillary pressures. The benefits of this approach compared with other methods are that it saves time, user-friendly and faster. It is reliable for estimating relative permeability and capillary pressures at steady state or unsteady state, imbibitions or drainage process either in oil or gas recovery. Copyright 2014, Offshore Technology Conference.